The complex interplay of Selenoprotein P, NO metabolites, and pancreatic enzymes in chronic pancreatitis and hypothyroidism is partially orchestrated by the SEPP1 gene’s rs7579 polymorphism: focus on gender aspect (Bangladesh Journal of Medical Science, 2024)
Objective To establish the association of the SEPP1 gene’s (rs7579) polymorphism with enzymatic, metabolic and hormonal activity in patients with chronic pancreatitis (CP) and primary hypothyroidism. Materials and methods Eighty CP patients (40 with comorbid hypothyroidism) and 30 healthy controls participated in the case-control study. Pancreatic enzymes, Selenoprotein P, NO metabolites (NO2 -+NO3 -), glucose, total cholesterol (TC), triglycerides (TG) and low/high density lipoprotein cholesterol (LDL-, HDL-C), Atherogenicity Index (AI), thyroid-stimulating hormone (TSH), Thyroxine (T4), glomerular filtration rate (GFR) were studied. SEPP1 (rs7579) genotyping performed by PCR (FlexCycler BU). Results and discussion SEPP1 (rs7579) gene’s A-allele increases the risk of hypothyroidism twice in CP [OR=2.0; OR 95%CI:1.09-3.66; р=0.023]. Pancreatic patients with hypothyroidism and SEPP1 gene’s (rs7579) AA-genotype had 60.0% (рАА=0.013) lower elastase and 13.78% (р=0.003) higher α-amylase as well as TSH by 10.81% (рАА=0.009) and 15.64% (рАА=0.009), especially in women 14.55-45.18% (р